Combined simulation of micro and nanoparticles in RF inductively coupled plasma torches with the variations of metallic species and feeding nozzle location. (1st January 2023) - Cheon, Cheongbin; Kim, Ho Jun; Lee, Hae June
Abstract: Lagrangian scheme for microparticles and Eulerian scheme for nanoparticles are combined to analyze the synthesis of metal nanoparticles in an RF plasma torch. It was observed that the evaporation occurs actively in the hot region of the inductively coupled plasma torch and generates the monomer source. As a result, monomers are consumed for the nucleation and the condensation of microparticles and nanoparticles. By changing the location of the feeding nozzle, it is possible to control the size distributions of the synthesized nanoparticles and microparticles. Furthermore, the size distributions of silver, gold, copper, and iron particles are simulated by controlling the temperature profiles at the loading position. The nanoparticle size distribution is adjustable by the temperature fields near the injection position, affecting the melting of microparticles for given physical properties of the boiling point, the melting point, and surface tension per species.